Effectiveness of Online Self-Help for Suicidal Thoughts: Results of a Randomised Controlled Trial - van Spijker, Bregje A. J. (Public Library of Science, 2014)
BACKGROUND: Many people with suicidal thoughts do not receive treatment. The Internet can be used to reach more people in need of support. OBJECTIVE: To test the effectiveness of unguided online self-help to reduce suicidal thoughts. METHOD: 236 adults with mild to moderate suicidal thoughts were randomised to the intervention (n = 116) or a waitlist control group (n = 120). Assessments took place at baseline, and 2, 4 and 6 weeks later. Primary outcome was suicidal thoughts. Secondary outcomes were depressive symptoms, anxiety, hopelessness, worry, and health status. RESULTS: The intervention group showed a small significant effect in reducing suicidal thoughts (d = 0.28). Effects were more pronounced for those with a history of repeated suicide attempts. There was also a significant reduction in worry (d = 0.33). All other secondary outcomes showed small but non-significant improvements. CONCLUSIONS: Although effect sizes were small, the reach of the internet could enable this intervention to help many people reduce their suicidal thoughts. TRIAL REGISTRATION: Netherlands Trial Register NTR1689